Performance and Quality Evaluation of the External Alarm System Based on ISO/IEC 25010 Standards - M Aidil Irawan (Journal of Computer Science Application and Engineering (JOSAPEN), 2026)
This study evaluates the performance and quality of an external alarm system using the ISO/IEC 25010 software product quality model. The evaluation focuses on eight quality characteristics, namely functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability, to provide a comprehensive assessment of the system. A quantitative approach was employed, and data were analyzed using a measurement model to test construct validity and reliability. The results of the validation test show that all indicators have outer loading values above 0.70 and Average Variance Extracted (AVE) values exceeding 0.50, confirming satisfactory convergent validity. Reliability testing also indicates strong internal consistency, with Cronbach’s Alpha and Composite Reliability values for all constructs exceeding the recommended threshold of 0.70. These findings demonstrate that the proposed measurement model is valid and reliable for evaluating external alarm systems. Overall, the study confirms that ISO/IEC 25010 provides a robust and effective framework for assessing software quality and performance in safety-critical alarm systems.